EFFORTS TO IMPROVE THE SATSAMAPTA PATROL TO PREVENT THE CRIMINAL ACTION OF WEIGHTING THEFT IN THE JURISDICTION OF THE PEMALANG - EKO PRASETYO (Police Studies Review, 2022)
The research in this thesis is motivated by the high crime of theft with weights in the Pemalang Police area, accompanied by increasing cases of theft with weights in the last 3 years. The National Police has the task of carrying out preventive actions through patrols as regulated in Perkabaharkam No.1 of 2017 concerning patrols. This study aims to determine the implementation of patrols carried out by the Pemalang Police Satsamapta and analyze the factors that influence it, as well as determine the efforts that must be made so that the patrols are carried out more optimally. In the conceptual literature the author uses the concept to analyze various problems. The concepts used include: the concept of patrol, the concept of effort and the concept of theft with weights. Meanwhile, the theoretical basis used are: Management Theory, and Crime Prevention Theory. This research was conducted with a qualitative approach, the type of case study research and data collection techniques with interviews, observations, and document studies. In this study also used Field Research Methods (Field Research) and used triangulation of data, sources, and theoretical to obtain data validity. From the results of the research, the initial conditions indicate that the implementation of patrols has not been maximized, especially with regard to implementation, member capabilities, procedures carried out, and organization. This is influenced by several factors, namely internal and external factors. Internally, the organization is constrained by every element, including personnel, budget, materials for carrying out patrols, methods, targets, facilities and infrastructure. Meanwhile externally, namely the Covid-19 pandemic, lack of legal awareness of the community, regional conditions, economic factors, and lack of awareness from the public. Based on the conditions that occurred, the authors compiled various problem solving and creative breakthroughs that could be made to improve the implementation of patrols, and could be used as an effort to increase the patrols of the Pemalang Police Satsamapta.